Where does Münch flow begin? Sucrose transport in the pre-phloem path - Rockwell, Fulton E; Gersony, Jessica T; Holbrook, N Michele (Current opinion in plant biology, 2018)
•High transpiration induces plasmodesmal convection of sugar away from the phloem.•Diffusion then overcomes convection and ensures a net flux of sugar to the phloem.•Convection and diffusion work in the same direction for very low transpiration.•Assimilation, path-length and diffusivity set the transpiration rate of the switch. Current conceptions of sucrose export largely neglect the effect of transpiration-induced water potential gradients within leaf mesophyll, even as the mix of convection and diffusion in the pre-phloem path remains uncertain. It is also generally held that the relative importance of convection and diffusion in the pre-phloem path is controlled by the ratio of their respective mass transfer coefficients. Here, we consider pre-phloem sucrose transport in the presence of adverse water potential gradients, finding that whether convection impedes or aids sucrose delivery to the phloem is independent of the permeability of the plasmodesmata to bulk flow, and depends only on assimilation rate, path-length, and the diffusivity. For most tissues subject to transpiration, convection through plasmodesmata pushes sugar away from the phloem.